The aesthetics of vision in the poem of supplication in the models of the poetry of Asir region - Al-Jaloub, Taher Massad Saleh; Al-Hussami, AbdulHamid Saif Ahmed (Arab Journal for Sciences and Research Publishing, 2019)
This study is based on the hypothesis that the vision of the poem (the evangelism)- the transfer of the self- confessed mysteries to the divine self- is its aesthetic peculiarity, which distinguishes it from the vision of other poetic models such as the poem of the spinning, the praise and the lamentation for mere representation. The choice was made to test this hypothesis on the poetry of the Asir region; to clarify the specificity of the vision of the poem in the fabric of its texts; interacting with a striking intimacy with the values ​​of the poet's spiritual surroundings, which leads poets to speak to the divine; Thus, the study reduced its problem with the question: What is the aesthetic peculiarity of a poem in the poetry of Asir? The nature of the subject dictated to the researcher to adopt the mechanism of discourse- according to the theories of critic Henry Mishonic- whose task is to clarify the relationship between the structures of poetic discourse, and the specificity of the self- poet involved. The study plan consists of an introduction, a preface, two papers, and a conclusion. The second is the world of the divine self, which is characterized by the absolute ability to resolve the rift, and the second is the world of the divine self, Serenity, support for the defeated, and the relief of the Mujahedeen.
Keywords: vision; poem; poetry; Asir region